2015
DOI: 10.1039/c5ra13533h
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide immobilized with ionic liquids: facile preparation and efficient catalysis for solvent-free cycloaddition of CO2to propylene carbonate

Abstract: Functionalized imidazolium-based ionic liquids (ILs) with different halides (Cl, Br, and I) were successfully immobilized on the surface of graphene oxide materials by one step through covalent condensation between alcoholic hydroxyl groups of GO and alkoxyl groups of functionalized ILs. Several characterization including TG, Raman, AFM, FT-IR, and XPS techniques have been applied to 10 characterize the physicochemical properties of the synthesized GO-[SmIm]X materials. In the solventfree cycloaddition reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…From these images, the lamellar structure of GO and HBPSi-GO are clearly observed. Figure 3a shows the thickness of single-nanolayer GO after ultrasonication is 1.0-1.3 nm, which is consistent with the previous reports [29]. By contrast, the functionalized GO reveals an average thickness of 3.2-5.0 nm.…”
Section: Hbpsi-go Characterizationsupporting
confidence: 90%
“…From these images, the lamellar structure of GO and HBPSi-GO are clearly observed. Figure 3a shows the thickness of single-nanolayer GO after ultrasonication is 1.0-1.3 nm, which is consistent with the previous reports [29]. By contrast, the functionalized GO reveals an average thickness of 3.2-5.0 nm.…”
Section: Hbpsi-go Characterizationsupporting
confidence: 90%
“…Imidazolium based silane was also grafted onto the surface of GO obtaining material 112 (Scheme ), which was used as active and recyclable catalyst for the CO 2 cycloaddition to produce cyclic carbonates . In this paper the authors highlighted the fundamental role played in the catalytic process by the residual functional groups of GO acting as hydrogen bond donors.…”
Section: Graphene‐ Graphene Oxide‐ and Reduced Graphene Oxide‐based mentioning
confidence: 99%
“…Catalysts 2019, 9, x FOR PEER REVIEW 23 of 30 activity within 4 h, using 2 MPa CO2 at 120 °C for 33 and at 90 °C for 34, and they were reused for five consecutive catalytic cycles without significant loss of activity. Li et al reported the preparation of a series of imidazolium-based IL grafted onto the surface of GO, used as active and recyclable catalysts for CO2 cycloaddition to produce cyclic carbonates [100]. Hybrid material 35 endowed with iodide counteranions (Scheme 26) resulted as the best-performing catalyst (2 MPa pressure of CO2 at 140 °C for 4 h), although 600 mg of modified GO were used for 15 mL of epoxide.…”
Section: Scheme 22mentioning
confidence: 99%
“…Li et al reported the preparation of a series of imidazolium-based IL grafted onto the surface of GO, used as active and recyclable catalysts for CO 2 cycloaddition to produce cyclic carbonates [100]. Hybrid material 35 endowed with iodide counteranions (Scheme 26) resulted as the best-performing catalyst (2 MPa pressure of CO 2 at 140 • C for 4 h), although 600 mg of modified GO were used for 15 mL of epoxide.…”
Section: Scheme 22mentioning
confidence: 99%